Substitution of Potato with Cempedak Seeds in Making Potato Donuts - Kalista Syifa Ashila; Teddy Chandra; Lien Maulina (NHI HOSPITALITY INTERNATIONAL JOURNAL, 2025)
Purpose of the study: This study aims to (1) assess the final appearance of donuts made with cempedak seeds, (2) evaluate the aroma produced, (3) examine the texture achieved, and (4) determine the taste of donuts incorporating cempedak seeds as a key ingredient. Design/methodology: The study employs an experimental research design, in which donuts were produced using cempedak seeds, the preparation process was systematically observed from beginning to end, and the outcomes were recorded to generate a report that can be presented and evaluated. Finding: The results indicate that cempedak seeds can serve as a viable substitute for potatoes in potato donut production and are well accepted by panellists in terms of sensory attributes. Research limitations/Implications: This research offers potato donut producers an alternative ingredient option to potatoes, potentially supporting product diversification and innovation in donut production. Novelty/Originality of the study: This study is among the first to explore cempedak seeds as an alternative raw material in potato donut production, providing empirical evidence on their sensory performance and potential application in local food product development